Prognostic impact of pretreatment serum superoxide dismutase activity in patients with locoregionally advanced nasopharyngeal carcinoma. Issue 1 (March 2022) - Qiu, Wenze; Jiang, Jiali; Zhan, Zejiang; Huang, Laiji; Deng, Jin; Ye, Jiacai; Li, Guo; Liao, Kai; Zhang, Huanhuan; Ding, Yan; Yuan, Yawei; Zheng, Ronghui
Purpose: To evaluate the prognostic effect of pretreatment serum superoxide dismutase (SOD) activity in locoregionally advanced nasopharyngeal carcinoma. Methods: A total of 498 patients diagnosed with stage III–IVA nasopharyngeal carcinoma between January 2013 and December 2016 were involved in this study. The X-tile program was used to determine the cut-off value of pretreatment serum SOD activity based on disease-free survival. Kaplan–Meier methods and Cox proportional hazards models were used to evaluate the impact of serum SOD levels on survival outcomes. The receiver operating characteristic (ROC) curve analysis was used to compare the prognostic value of clinical stage, pretreatment serum SOD level, and the combination of them regarding disease-free survival. Results: Based on the X-tile plot, the optimal cutoff value of pretreatment serum SOD activity for disease-free survival was 146.0U/mL. As a dichotomous variable, SOD was significantly higher in non-keratinizing differentiated disease ( P  = 0.027) and early T stage ( P  = 0.011). Compared with the lower subset, higher SOD activity predicted an inferior 3-year rates of overall survival (84.6 vs. 94.7%, P  < 0.001), distant metastasis-free survival (78.3 vs. 92.8%, P  < 0.001) and disease-free survival (78.2 vs. 92.8%, P  < 0.001). Multivariate analysis verified that the SOD activity was an independent prognostic indicator to predict distant metastasis, disease progression, and death. The area under the ROC curve (AUC) of the combination was superior to that of clinical stage or SOD alone for disease-free survival (both P  < 0.01). Conclusion: Serological SOD activity before treatment is an important prognostic indicator for patients with stage III–IV non-metastatic nasopharyngeal carcinoma undergoing chemoradiation therapy.